Vaginal rupture and evisceration related to contact ulcer due to prolapsed uterus: case report - Sandoval - Paredes, José (2021)
Vaginal evisceration occurs in 0.36% to 0.96% of women undergoing hysterectomy. It is most frequently caused by dehiscence of the vaginal vault after hysterectomy, and there is higher risk for this occurrence after laparoscopic hysterectomy compared to an open approach. We present the case of a 63-year old woman with a complete uterine prolapse, with no past surgical history, who was admitted to the Emergency Department because of vaginal evisceration. The rupture occurred in the posterior vaginal wall where a contact ulcer had formed. A laparotomy was performed, aiming to put the intestine back in its place and to repair the tear on the vaginal wall. The prolapse was corrected eight months later, with a satisfactory outcome. The technique for surgical repair depends upon the type and viability of the herniated organ, and the procedure may be performed using a vaginal, abdominal, or combined approach, through laparotomy or laparoscopy.